Metode Demonstrasi Pemberian Makan Sebagai Upaya Peningkatan Pengetahuan dan Sikap Ibu Dalam Memberikan Makan pada Bayi 6-12 Bulan - Emma Anastya Puriastuti; Budi Utomo (EMBRIO, 2021)
Complementary feeding is food given to babies starting at the age of 6 months. The main obstacle using MP-ASI is due to the lack of correct knowledge about MP-ASI, one of which is through counseling. The right selection method and media will affect the mother's knowledge and attitude in feeding. The purpose was to determine the effect of demonstration method on increasing mother’s knowledge and attitudes in feeding infants 6-12 months. The research design used pre-experimental with one group pretest posttest. Samples were obtained from quota sampling as many as 32 respondents and located in Krembangan village, Surabaya. The instrument used an instrument of knowledge and attitudes related to feeding that has been validated. Data analysis using Wilcoxon test. The results showed that the mother's knowledge after being given the demonstration method increased (87.5%) (p = 0.001) and the mother's attitude increased (71.9%) (p = 0.009) compared to before the demonstration method was given. The conclusion of this study is the demonstration method of feeding can increase mother’s knowledge and attitudes in feeding infants aged 6-12 months. This method can be chosen by midwives or nutritionists in educating mothers and cadres regarding how to feed infants aged 6-12 months.